2015
DOI: 10.11648/j.sr.20150303.20
|View full text |Cite
|
Sign up to set email alerts
|

Study on Variation in Seed Morphology, Oil Content and Fatty Acid Profile of Madhuca longifolia Grown in Different Agro-Climatic Zones in Sri Lanka

Abstract: Abstract:The aim of this study was to determine the variation in morphology of seeds, seed oil content and the fatty acid profile of M. longifolia and, to find the relationship between oil content and fatty acid composition with environmental conditions. Seeds were collected representing four agro-climatic zones in Sri Lanka. The length (2.7333-3.4333 cm), width (1.0633-1.2967 cm) and the weight (0.9262-1.4018 g) were determined in seeds. Significant differences were there within agro-climatic zones. Oil from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…The oil obtained after extraction was pale yellow and having a characteristic odor. The average oil content in the seed was 57.59 %, which was higher as compared to previous reports 11,12 . The high oil content in M. longifolia seeds is an important parameter for the economic view and industrial applications 13,15 .…”
Section: Resultscontrasting
confidence: 67%
“…The oil obtained after extraction was pale yellow and having a characteristic odor. The average oil content in the seed was 57.59 %, which was higher as compared to previous reports 11,12 . The high oil content in M. longifolia seeds is an important parameter for the economic view and industrial applications 13,15 .…”
Section: Resultscontrasting
confidence: 67%
“…They also recorded higher levels of essential amino acids like lysine, valine, methionine, isoleucine and leucine in MOC compared to GNOC. The fatty acid profile of MOC has been studied in detail by several workers (Marikkar and Yanty, 2012;Kulkarni et al, 2013;Munasinghe and Wansapala, 2015;Ramadan et al, 2016). They reported that the seed of mahua in different climatic conditions contains fat in the range of 40-54% which is in the form of oil at ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…If the extracted Mee fat was properly purified, it could use for edible purposes. Mee fat has a beneficial fatty acid profile with low saturated fatty acid content [7]. Approximately 250 mL of fat can be extracted from 1 kg of Mee seeds [4].…”
Section: Value-added Products From Mee Fruits and Seedsmentioning
confidence: 99%
“…The use of Mee fat in the food industry has been carried out on a limited scale. According to past reports, applications of this seed fat are limited mostly due to the lack of technical information regarding its properties and potential uses [7]. Semi-solid Mee fat is used in cooking, adulteration of ghee, and manufacturing chocolate.…”
Section: Defatted Mee Seed Cakementioning
confidence: 99%
See 1 more Smart Citation